Psychological features of motivation of athletes in the aspect of theoretical analysis - Loseva S.N. ,; Sadigov G.I. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify scientific aspects of considering the phenomenon of sports motivation as a psychological feature of athletes. Methods and structure of the study. Theoretical research methods were used: comparative typological (of great importance when analyzing literature on a research problem), method of generalization and systematization (generalization of concepts and definitions, establishment of general properties and characteristics based on scientific research in working with sources). Results and conclusions. The role of motivation in psychological science is defined, historical aspects of the study of motivation are described, and features of the manifestation of sports motivation are identified. The concept of personality in psychology is also defined, the specifics of the mental state of an athlete’s personality in the process of forming sports motivation are revealed. The findings reflect the key role of motivation in shaping attitudes towards sport, particularly during the formative years, highlighting the need for a meaningful approach to motivation research. This approach focuses on the significant influence of the social environment, nurturing strong self-esteem and realistically shaping athletes' aspirations, which ultimately improves mental toughness, determination and overall commitment.